The potential of coffee husk biochar for chromium removal from acid mine drainage using constructed wetlands - Titania, Opi Mida; Fahruddin, Fahruddin; Latunra, Andi Ilham (Journal of Degraded and Mining Lands Management, 2026)
This study aimed to characterize physicochemical properties of biochar generated from coffee husks and assess its efficacy in the removal of chromium (Cr) from acid mine drainage (AMD) using a constructed wetland system. The biochar was made through pyrolysis and then chemically activated with H?PO? and KOH to enhance its adsorption. Characterization results showed increased surface area and porosity, and that functional groups such –OH, –COOH, and C=O were present, which are good for metal binding. In the experiment, 5 g of biochar (T2) reduced the amount of Cr from 59.53 ppm to 4.47 ppm in 12 days, which was better than other amounts of biochar applied. The study observed significant reductions in sulfate content and improvements in pH. The sulfate levels in T2 went down from 176.78 mg/L to 81.60 mg/L, while the pH increased from below 3 to 6.85. This shows that the acid was neutralized well. These improvements show that biochar not only absorbs contaminants but also lowers the acidity of AMD. The addition of mangrove sediment also enhanced the remediation process by using ion exchange, complexation, and microbial activity, especially from sulfate-reducing bacteria (SRB). The results show that coffee husk biochar, especially when combined with mangrove sediment, is a sustainable and eco-friendly material for treating heavy metal-contaminated acidic wastewater.